Food Insecurity in Northwest Wisconsin : Lessons from Eau Claire - Wiedenfeld, Noah (My University, 2012)
There is an ongoing and increasingly divisive fight over food stamps in the United States. When it comes down to it, the "fight over food stamps" isn't solely about whether to help those with less financial means, but also the amount of freedom that lower-income people should have to choose what they eat. Food has become a policy issue rather than a basic human right. This study investigated Wisconsin's FoodShare program, the state-managed program for dispersing federal funds from the Supplemental Nutrition Assistance Program (SNAP), otherwise known as food stamps. This study will help separate facts from fiction about the Eau Claire food system in regards to low-income citizens' access to healthy food and their purchasing habits. Such an understanding is essential to effective policy-making at both local and state-wide levels.
Color poster with text, maps, tables, graphs, charts, and images.
Keywords: Food security--Wisconsin--Eau Claire; Food stamps--Wisconsin; FoodShare Wisconsin; Posters; Hunger--Wisconsin--Chippewa River Valley